Photolabile Ru Model Complexes with Chelating Diimine Ligands for Light‐Triggered Drug Release. Issue 13 (1st February 2018) - Battistin, Federica; Balducci, Gabriele; Wei, Jianhua; Renfrew, Anna K.; Alessio, Enzo
Abstract : A series of water‐soluble photolabile model complexes of the general formula [Ru([9]aneS3 )(chel)(py)]Cl2 ([9]aneS3 = 1, 4, 7‐trithiacyclononane, chel = chelating diimine) was prepared and fully characterized. The phototriggered release of pyridine with visible light as a function of the nature of the diimine chel = 2, 2′‐bipyridine (6 ) 1, 10‐phenanthroline (7 ), 4, 7‐diphenil‐1, 10‐phenanthroline (8 ), dipyrido‐[3, 2‐ a :2′, 3′‐ c ]phenazine (dppz, 9 ), 2, 2′‐biquinoline (bq, 10 ) was investigated. Our aim is to establish whether this type of complexes might be realistically used in the photo‐uncaging strategy of photoactivated chemotherapy (PACT) in the future. Compounds6 –9 present a MLCT absorption in the blue region of the visible spectrum. When irradiated with light at 470 nm, they rapidly and quantitatively release the coordinated pyridine. Complex10 turned out to be quite different from the others in the series. Structure‐wise, in10 the average plane of coordinated bq – owing to its steric demand – is remarkably tilted relative to the equatorial coordination plane [37.43(4)°, with the "front" of the ligand pointing towards the axial py] and the orientation of py is nearly orthogonal compared to that found in6 and7 for minimizing steric clashes with bq. The low‐lying acceptor orbitals of bq induce a red‐shift of the MLCT absorption maximum to ca. 500 nm. Contrary to the expectations, complex10 is more photostable compared to6 –9 and photo‐dissociation of both py and bq, in nearly equal amounts, occurs. A detailed theoretical investigation was performed on10 (and on6 for comparison), for explaining its peculiar spectral features and photochemical behavior. Abstract : The light‐induced release of pyridine from a series of water‐soluble model complexes of the general formula [Ru([9]aneS3 )(chel)(py)]Cl2 ([9]aneS3 = 1, 4, 7‐trithiacyclononane, chel = chelating diimine) was investigated with the aim of establishing whether this type of complexes might be realistically used in the photo‐uncaging strategy of photoactivated chemotherapy (PACT).